Upaya Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Melalui Painting Play Di TK Adz Dzikra Auzi - Nurhaliza Heldiana; Ristra Sandra Ritonga (Journal on Education, 2025)
This research aims to improve the fine motor skills of young children through painting play activities at Adz Dzikra Auzi Kindergarten, Lama Village. Based on observations, many children have difficulty developing fine motor skills such as hand-eye coordination and grip strength. Therefore, this research uses the classroom action research (PTK) method which is carried out in two cycles. The results of the study showed significant development in children's fine motor skills, especially in hand and eye coordination, grasping strength, and stabbing in applying the cat. Apart from that, there was an increase in children's creativity and independence in painting play activities. The research results showed significant development in children's fine motor skills: Hand and Eye Coordination: Increased from 26.7% at the initial meeting to 40% in the next cycle, with more children reaching the BSB (Very Well Developed) category. Finger and Grip Strength: Initially only 33.3%, but increased to 40% in the second cycle. Accuracy in Paint Application: Experienced an increase from 40% to 40% in the BSB category, indicating increased child control and precision. Apart from that, this research also found that playing painting activities contributed to increasing children's creativity and independence. Children are bolder in expressing ideas through colors and shapes, and more independent in completing their assignments. Thus, painting play activities have proven to be effective in improving the fine motor skills of young children, as well as having a positive impact on the development of their creativity and abilities.